Tropospheric response to gulf stream intrinsic variability: a model ensemble approach - Chakravorty,S; Czaja,A; Parfitt,R; Dewar,WK (Geophysical Research Letters, 2024)
The Gulf Stream's (GS) impact on the marine boundary layer (MBL) is well established, yet the mechanisms and timescales through which it affects the upper-troposphere and contributes to precipitation are debatable. Using a high-resolution regional atmospheric model, we shed light on the impact of ocean intrinsic variability (OIV) along GS on midlatitude-atmosphere. Taking advantage of a 24-member ensemble of ocean model integrations, we devised a novel experimental setup where the same weather system feels different realizations of GS sea surface temperature (SST). We introduce the “Eddy Recharge-Frontal Lift” (ERFL) mechanism, highlighting the joint importance of synoptic variability and boundary layer processes. ERFL mechanism proposes that OIV recharges/discharges MBL with moisture and heat, while convergence associated with passing atmospheric-fronts uplifts these MBL-trapped anomalies to upper-troposphere and imprints on precipitation in surprisingly short periods (a month). The impact of OIV on precipitation depends on the background mean SST.